O tratamento da variação linguística nos gêneros discursivos da prova de Língua Portuguesa (linguagens, códigos e suas tecnologias) do Enem (1998-2018) à luz da sociolinguística variacionista e educacional - Rech, Elisangela (2020)
This research work aims to investigate the treatment of linguistic variation in the ENEM Language Test, Codes and its Technologies - Portuguese Language from 1998 to 2018 in the light of Variationist Sociolinguistics and Educational Sociolinguistics. Initially, we briefly summarize the historical course, the constitution and the characteristics of the LEM - LP Test of ENEM in the period of 20 years. We also carried out a bibliographic survey of some studies on linguistic variation in the LEM - LP test at ENEM. Following, we present the theoretical and methodological contribution of Variationist Sociolinguistics, according to Weinreich, Labov and Herzog ([1968] 2006) and Labov ([1972] 2008), of Educational Sociolinguistics (BORTONI-RICARDO, 2004; 2005) among others. Then, we discuss the methodological decisions adopted, from the perspective of qualitative and quantitative analysis. Afterwards, we dedicate ourselves to the analysis of the treatment of linguistic variation in the LCT - LP Test at ENEM. Our survey resulted in 89 objective questions that are directly linked to the phenomenon of linguistic variation. We found that this theme was more frequent in the second phase of ENEM than in the first phase. In our sample, we did not find any issue related to the treatment of linguistic variation in the years 1999 and 2003, which is different from what is recommended by official documents. As for the type of variation, we identified nine different types related to the internal and external dimension of the variation, which demonstrates the need for the theme to be addressed with greater assessment by the teacher of the Portuguese Language curriculum component in school institutions. The questions involving phenomena related to the social dimension were more recurrent than those covering the linguistic dimension. We also found diversity in the use of discourse genres in the two periods of analysis. Our results also revealed that the genres of the written modality are more recurrent than those of the oral modality and the hybrids (written and oral). As for the discursive domain, fictional genres were the most recurrent in the Exam, followed by instructional and journalistic ones and, to a lesser extent, the genres of the advertising, interpersonal, legal, commercial, leisure and religious discourse domains. Finally, when we opted for the analytical resource of continuous orality-literacy, we found that most of the discursive genres present in the LCT - LP Objective Proof are located in literacy events although we have also found genres located, in a smaller quantity, in events of literacy. orality. Thus, it is suggested to increase the genres focused on orality in ENEM, since the documents support the modality and also because it is a way to further encourage ENEM candidates to reveal the “linguistic chameleon” that each one carries within them.